Parenting Self-Efficacy Skills, Well-Being of Kenyan Teenage Mothers & Involvement in Learning of Their Preschool Children (Global Journal of Human-Social Science, 2024)
This study provides an in-depth insight into the lived experiences of teenage mothers experiences of schooling stigma and gender narratives of the way in which they experience motherhood The girls often bare teenage pregnancy consequences and men who are responsible are often less seen in the consequences and narratives of teenage pregnancy The African culture sees young girls as those having to care and raise the children also exacerbates the way in which teenage mothers and particularly those in this study experience motherhood Using a survey the study examines 112 Kenyan teenage mothers parenting self-efficacy skills financial and emotional stress and corelate that to their involvement in their young children s learning in preschool programs Results find that financial and emotional stress plays a huge role in how teenage mothers engage in their children s learning